How to be good at science, technology & engineering - Dinwiddie, Robert; Farndon, John; Gifford, Clive; Harvey, Derek; Morris, Peter; Rooney, Anne; Setford, Steve; Morgan, Ben; Gahir, Sunita; Radcliffe, Peter; Brown, Shaila; Sandford, Laura; et al. (London : Dorling Kindersley Limited, 2018)
Little scientists will understand science in seconds with this essential homework-helping guide. Learn about everything from molecules and magnetism to rockets and radio waves and find out how a hot-air balloon rises, how erosion flattens mountains, how light waves zip through space, and how the human eye sees colours! With STEM (science, technology, engineering, and maths) subjects ever more important in today's technological world, How to be Good at Science, Technology, and Engineering is the perfect book to inspire and educate inquisitive young minds and prepare them for the future. This is the perfect homework guide for parents and their children, with all core curriculum areas of science included. Cool illustrations show the appliance of science in the real world: see how microchips, tractors, and suspension bridges work. Hands-on projects feature fun experiments to try at home or school: try polishing old coins in vinegar, or make an erupting volcano with baking soda.
Keywords: Science -- Juvenile literature; Technology -- Juvenile literature; Engineering -- Juvenile literature